Managing pain and distress in children undergoing brief diagnostic and therapeutic procedures - Trottier, Evelyne D (Paediatr Child Health, 2019)
Common medical procedures to assess and treat patients can cause significant pain and distress. Clinicians should have a basic approach for minimizing pain and distress in children, particularly for frequently used diagnostic and therapeutic procedures. This statement focuses on infants (excluding care provided in the NICU), children, and youth who are undergoing common, minor but painful medical procedures. Simple, evidence-based strategies for managing pain and distress are reviewed, with guidance for integrating them into clinical practice as an essential part of health care. Health professionals are encouraged to use minimally invasive approaches and, when painful procedures are unavoidable, to combine simple pain and distress-minimizing strategies to improve the patient, parent, and health care provider experience. Health administrators are encouraged to create institutional policies, improve education and access to guidelines, create child- and youth-friendly environments, ensure availability of appropriate staff, equipment and pharmacological agents, and perform quality audits to ensure pain management is optimal.